FABRIK-R: An Extension Developed Based on FABRIK for Robotics Manipulators - Matheus C. Santos (IEEE Access, 2021)
This paper develops on the process of inverse kinematics (IK) for manipulator robots based on a recent technique from the computer graphics area that has been highlighted by its simplicity and low computational cost. This IK solver is known as Forward And Backward Reaching Inverse Kinematics (FABRIK) suffers from singularities when applied in kinematic chains composed of one degree of freedom (1-DOF) joints. Some extensions of this method have been proposed to incorporate the constraints in some of the most common joints, however, their application over kinematic chains with only 1-DOF joints is still not possible. Since several manipulators have kinematic chains composed of 1-DOF joints, this work presents a new method, named FABRIK-R, to extend the original method for applications in the robotics manipulators field.